The Influence of Service Quality, Digital Customer Experience, and Brand Image on Customer Satisfaction of the I.Saku Application in Bandung City - Adi Suparwo; Shafna Nur Halizha; Feti Fatimah Mauliyan (Universitas Mercu Buana, 2026)
With the advancement of technology, it is easier for people to make cash transactions without cards using e-wallets. The rise of e-wallets today makes users consider more about the quality of service, ease of usage, brand image from e-wallet when they want to use it. This research seeks to examine the effect of service quality, digital customer experience and brand image to customer satisfaction for the I.Saku Application in Bandung City. Descriptive and verification research methodologies are used in this study’s through a quantitative method. The object is studied in this study were customers of the I.Saku Application in Bandung City using a total 100-person sample. The sampling method regulated in this case research is the nonprobability sampling method with purposive sampling technique. Statistics data this study uses multiple linear regression data analysis with the help of statistical processing of data tools bye using IBS SPSS statistic 25 application. The findings of this study illustrate that partially the service quality variable has a significant effect on customer satisfaction of the I.Saku Application in Bandung City and brand image has a significant effect on customer satisfaction of the I.Saku Application in Bandung City. Meanwhile, digital customer experience does not have a significant effect on customer satisfaction of the I.Saku Application in Bandung City. Simultaneously, service quality, digital customer experience and brand image have a joint effect on customer satisfaction of the I.Saku Application in Bandung City.